Self-Reported Population Health: An International Perspective based on EQ-5D - Szende, Agota; Janssen, Bas; Cabases, Juan (Springer Netherlands : Imprint: Springer, 2014)
The EQ-5D instrument, as a standardized, cross-culturally validated measure of self-assessed health has a hugely important role in understanding population health within and across countries. Over the past two decades a wealth of international population health survey data have been accumulated by the EuroQol Group from research conducted in many countries across four continents. One of the success factors of the EQ-5D instruments has been the easy availability of national or international sets of EQ-5D data, as well as clear explanations and guidance for users. There is an unmet need to produce a comprehensive book that captures up-to-date and expanded information of EQ-5D self-reported health and index values. EQ-5D population norms and cross-country analyses are provided from representative national surveys of 20 countries and additional regional surveys. This book will be a must for those who believe that how people report and value health is very important.